Dynamics of Mother’s Psychological Condition As a Caregiver For Thalassemia Children - Yunike; Eprila (International Journal Scientific and Professional (IJ-ChiProf), 2022)
Globalization and the monetary crisis, apart from providing opportunities, also presented big challenges, because they could change the map of health services which could result in the development of service quality and accelerate technology transfer. Most of the female adolescents experience psychological disorders due to the complex attributes of adolescent women due to physiological changes in the body either expected or due to age, one of which is the biggest factor of psychological problems on the arrival of the menstrual period. This research is an exploratory case study with a cross sectional approach on psychological disorders of menstrual periods in teenage girls of SMAN 4 Baturaja. The research subjects are 383 students of grade X, XI and XII students. From the univariate results of menstrual period psychological disorders, mild, namely 223 respondents (58.2%) and heavy 160 respondents (41.8%). Age at first menstruation without risk was 369 respondents (96.3%) and at risk was 14 respondents (3.7%), weight without risk is 276 respondents (72.1%), and at risk is 107 respondents (27.9%). menstrual cycle, regular was 203 respondents (53%) and irregular were 180 respondents (47%). During menstruation, mild pain was 70.2% of respondents and severe pain was 114 respondents (29.8%). Based on the bivariate results of the first menstrual period, the p-value was 0.050, body weight obtained a p-value of 0.004, the menstrual cycle was obtained p-value of 0.002 , the menstrual period obtained a p-value of 0,000. There is a relationship between age at first menstruation, body weight, menstrual cycle and menstrual pain with psychological disorders in teenage students